Using a PCR instrument to hydrolyze polysaccharides for monosaccharide composition analyses. (15th July 2020) - Zhang, Meng; Zhang, Yiran; Ma, Xuexiao; Liu, Xiangping; Niu, Min; Yao, Ruyong; Zhang, Lijuan
Graphical abstract: Highlights: A facile and time-saving method is developed for polysaccharide hydrolysis. Excellent reproducibility and easy to operate. High throughput sample processing (up to 96 samples) at one time. Abstract: Monosaccharide composition analysis after acid hydrolysis is the first step towards structural characterization of the polysaccharides. To modernize the hydrolytic procedure, we used a polymerase chain reaction (PCR) instrument to accomplish the task, which allows to generate monosaccharide products from up to 96 samples simultaneously within 30 min. Fucoidan, chitosan and propylene glycol alginate sodium sulfate (PSS) were chosen as representatives of complex, basic and acidic polysaccharides to optimize the hydrolytic conditions, respectively, through the orthogonal L9 (3 4 ) experiments. The hydrolysis loss ratio for monosaccharide standards were also measured. Using this assay, the hydrolysis plus 1-phenyl-3-methyl-5-pyrazolone (PMP) labeling of the monosaccharide products could be accomplished in 90 min with the RSD values less than 5 % based on HPLC analysis. We further confirmed the reliability of the assay by HPLC coupled MS analysis. In conclusion, PCR instrument-based hydrolysis assay is suitable for monosaccharide composition analysis of complex, acidic and basic polysaccharides.